2005
DOI: 10.1016/j.cardiores.2004.10.009
|View full text |Cite
|
Sign up to set email alerts
|

?- but not ?-adrenergic receptors precondition the ischemic heart by a staurosporine-sensitive, chelerythrine-insensitive mechanism

Abstract: These data demonstrate that alpha1A-ARs protect the heart from ischemic injury through a staurosporine-sensitive signaling pathway that is independent of protein kinase C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 40 publications
5
77
0
Order By: Relevance
“…While CAM-α 1A AR mice also display cardiac hypertrophy as in CAM-α 1B AR mice, α 1A AR activation results in positive adaptation of the heart to protect against ischemic damage through preconditioning via cardiac protective IL-6 and JAK/STAT pathways or by preventing apoptosis due to increased glucose uptake (Rorabaugh et al 2005;Papay et al 2013, Perez, unpublished data). In the current study, the only heart abnormality found in CAM-α 1A AR mice was a case of endocarditis/myocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While CAM-α 1A AR mice also display cardiac hypertrophy as in CAM-α 1B AR mice, α 1A AR activation results in positive adaptation of the heart to protect against ischemic damage through preconditioning via cardiac protective IL-6 and JAK/STAT pathways or by preventing apoptosis due to increased glucose uptake (Rorabaugh et al 2005;Papay et al 2013, Perez, unpublished data). In the current study, the only heart abnormality found in CAM-α 1A AR mice was a case of endocarditis/myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The CAM receptor genes were expressed under the endogenous promoters, and the animals have been previously characterized (Zuscik et al 2000;Rorabaugh et al 2005). The longevity part of the study included 235 mice, and the pathology study included 157 mice with some overlap.…”
Section: Animalsmentioning
confidence: 99%
“…Vatner and colleagues also reported a similar observation that cardiac denervation did not block early phase but did blunt late-phase ischemic preconditioning via ␣ 1 -adrenoceptor signaling (102). In search of effective receptor subtypes, Tsuchida et al showed the direct involvement of ␣ 1b -adrenoceptor in ischemic preconditioning (214), but studies using transgenic mice support cardioprotection by ␣ 1a rather than by ␣ 1b (160). On the other hand, the ␤ 2 -adrenoceptor is reported to confer cardioprotection in ischemic preconditioning (209), whereas preischemic ␤ 1 -activation could be an alternative (193).…”
Section: Factors Underlying the Mechanisms Of Preconditioningmentioning
confidence: 96%
“…For example, sustained transgenic activation of ␣ 1b -adrenoceptor did not elicit cardioprotection (160), whereas temporal blockade during the preconditioning period protected the myocardium (68,214). Also, ␤ 1 -adrenoceptor activation is reported to be beneficial during the preconditioning period but deleterious after reperfusion (193).…”
Section: Factors Underlying the Mechanisms Of Preconditioningmentioning
confidence: 99%
“…2,3 These data also raise the possibility that ␣1A subtype-selective agonist therapy might be cardioprotective, as also suggested by some recent studies with ␣1A-transgenic mice. 31,32 …”
Section: Circulation February 13 2007mentioning
confidence: 99%